Continuity and change in Romanian societal culture dimensions - Doina Catana; Gheorghe Alexandru Catana (Journal for East European Management Studies, 2012)
Our study contributes to the literature about societal culture dimensions, as reflected by the perceptions and expectations of students and present managers. We find some similarities but also statistically significant differences between students and middle managers in Romania in terms of their perception on nine societal culture practices as well as their expectations about societal culture values. The research sample consists of 427 undergraduate and graduate students in engineering and business and 216 middle managers. Our results show similarities in perceptions of society's future orientation, institutional collectivism and assertiveness and significant differences in perception of the other six cultural practices. Similarities in expectations (values) were also noted concerning gender egalitarianism and assertiveness. – – Unsere Studie liefert einen Beitrag zur Literatur über Nationalkulturen wie sie in den Sichtweisen und Erwartungen von Studenten und derzeitigen Führungskräften reflektiert werden. Wir fanden einige Übereinstimmungen, aber auch statistisch signifikante Unterschiede zwischen Studenten und mittleren Führungskräften in Rumänien bezüglich ihrer Sichtweisen auf neun kulturelle Werte. Das Sample bestand aus 427 Studenten ohne und mit Abschluss in Ingenieurwissenschaft und Betriebswissenschaft und 216 mittleren Führungskräften. Unsere Ergebnisse zeigen Übereinstimmungen in Sichtweisen auf die gesellschaftliche Zukunftsorientierung, den institutionellen Kollektivismus und die Selbstbehauptung, und signifikante Unterschiede in Hinblick auf die sechs anderen kulturellen Praktiken. Übereinstimmungen in Erwartungen (Werte) gab es auch betreffend geschlechtlichem Egalitarismus und Selbstbehauptung.
Keywords: 650; GLOBE; societal culture; cultural practice; cultural value